Phospho‐Proteomic Analysis of Cardiac Dyssynchrony and Resynchronization Therapy. Issue 19 (30th August 2018) - Stachowski, Marisa J.; Holewinski, Ronald J.; Grote, Eric; Venkatraman, Vidya; Van Eyk, Jennifer E.; Kirk, Jonathan A.
Abstract: Cardiac dyssynchrony arises from conduction abnormalities during heart failure and worsens morbidity and mortality. Cardiac resynchronization therapy (CRT) re‐coordinates contraction using bi‐ventricular pacing, but the cellular and molecular mechanisms involved remain largely unknown. The aim is to determine how dyssynchronous heart failure (HFdys ) alters the phospho‐proteome and how CRT interacts with this unique phospho‐proteome by analyzing Ser/Thr and Tyr phosphorylation. Phospho‐enriched myocardium from dog models of Control, HFdys, and CRT is analyzed via MS. There were 209 regulated phospho‐sites among 1761 identified sites. Compared to Con and CRT, HFdys is hyper‐phosphorylated and tyrosine phosphorylation is more likely to be involved in signaling that increased with HFdys and was exacerbated by CRT. For each regulated site, the most‐likely targeting‐kinase is predicted, and CK2 is highly specific for sites that are "fixed" by CRT, suggesting activation of CK2 signaling occurs in HFdys that is reversed by CRT, which is supported by western blot analysis. These data elucidate signaling networks and kinases that may be involved and deserve further study. Importantly, a possible role for CK2 modulation in CRT has been identified. This may be harnessed in the future therapeutically to compliment CRT, improving its clinical effects.